ALGORITHMIC ADVANCES: TRANSFORMING MSME SUCCESS PREDICTION IN MEXICO WITH GENETIC TECHNIQUES - Mendez, Juan CarlosProfessor; researcher, Tecnológico de EstudiosSuperiores de Ecatepec, Mexico; Ramírez, María Fernanda (Research Journal of Economics and Sustainable Development, 2024)
This paper presents a methodology based on genetic algorithms to determine the probability of success of Micro, Small, and Medium-sized Enterprises (MSMEs) in Mexico. The study emphasizes the importance of MSMEs in the Mexican economy and classifies them according to the number of employees and their range of annual sales based on the economic sector. The methodology integrates business plan indicators, socio-economic indicators, and INEGI information to determine the success of MSMEs. The study also analyses the causes of failure or closing of MSMEs, and proposes a methodology for determining the success of MSMEs. The authors apply the suggested methodology to newly created MSMEs in the transformation industry with economic development potential in the State of Sonora, Mexico. The study validates the methodology's effectiveness in predicting the probability of success of recently created MSMEs